Konsep Mahar Dalam Al-Qur’an: (Perspektif Syaikh Ahmad bin Mushtofa al-Farran dalam Kitab Tafsir Imam Syafi’i) - Iskandar Dzulqarnain; Abdul Natsir; Ni’matus Sholihah (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2026)
ABSTRACT This research aims to analyze and reconstruct Al-Farran's understanding of dowry, as well as place it in a comparative context with the views of other madhhabs and mufassir. The research method used is library research with a descriptive-analytical approach. Primary data is obtained from the Tafsir of Imam Shafi'i, while secondary data comes from books of tafsir, fiqh, and other supporting literature. The results of the study show that Al-Farran interpreted dowry (QS. An-Nisa': 4) as the absolute right of the wife (nihlah) which has a legal and philosophical dimension. He emphasized that dowry is a symbol of a husband's appreciation, earnestness, and responsibility, not just the price of a woman. Furthermore, Al-Farran does not limit dowry only to material possessions, but also accommodates non-material dowries in the form of benefits, such as the teaching of the Qur'an or hadith, as long as they have an agreed value. Comparatively, Al-Farran's view is in line with the Shafi'i School of Prayer which requires dowry, but it offers greater flexibility in the form of dowry. Keywords : Mahar, Al-Qur'an, Ahmad Musthafa Al-Farran, Tafsir Imam Shafi'i